Tinjauan Yuridis Wakaf Tanah Oloran di Wilayah Pesisir - Faiz Maharani; Agus Supriyo (Jurnal Hukum Lex Generalis, 2026)
Alluvial land is land formed by sedimentation in coastal areas that is often used as an object of waqf; however, legally it still holds the status of state land, thereby creating legal uncertainty. This study aims to analyze the legal administrative procedures for alluvial land as well as the legal certainty of its waqf status. The method used is a legal-normative approach, employing a legislative and conceptual framework through a literature review. The results of the study indicate that the legality of oloran land waqf depends on land rights status, registration procedures and the integration of land and waqf administration. Without legal certainty, waqf has the potential to lead to disputes. Therefore, regulatory strengthening is necessary to ensure legal certainty and protection for waqf.